Mineração e meio ambiente - discussão sobre a legislação pertinente e estudo de caso sobre a problemática da mineração social (minerais de uso na construção civil) - BASTOS, Luiz Tito Fernandes (2019)
In this study the problem of the social mining was approached, in other words, that related the exploration of the uses minerals in the building site (it sands, stone, gravel, other) and your impacts in the environment. It goes that, the study of it marries in loco was used in the municipal district of Salvaterra, located in the island of Marajó, in the Northeast of the State of Pará, where the stone explotação and it sands in the seafront of this municipal district it i done in the secret way by coachmen and caçambeiros. That illegal activity have been provoking along the years an increase in the rate of erosion of the waves and sea currents that reach the border of the municipal district, provoking the collapse of the ravines, progress of the tides, destruction of houses and roads and assoreamento of drainages. The studies showed that those effect were caused by the retreat of almost all the stones of natural protection formerly existent in the hillsides, and that absorbed the constant impacts of the waves when of the high tides. Without the stones the ravines were fragilizados and, consequently, there was the increase of the erosive process. The measured saneadoras, they plows suggested the urgent interference of the public power (municipal, state federal or) in order to of the to accomplish the effective environmental legislation. And, that it i made the necessary technical studies initially in the place, and adopted the reasonable measures of recovery of the areas degraded along the whole seafront of the Municipal district of Salvaterra, being avoided the worsening and the irreversibilidade of the strong erosion reinante in the place.